Flexible cycloalkyl substituents in insertion polymerization with α-diimine nickel and palladium species. Issue 7 (16th January 2020) - Dai, Shengyu; Li, Shuaikang; Xu, Guoyong; Wu, Cheng; Liao, Yudan; Guo, Lihua
Abstract : The investigation of the relationship between the structure of the catalyst and the microstructure of the obtained polymer has attracted much attention and broad interest in the field of transition metal-catalyzed olefin polymerization. Abstract : The investigation of the relationship between the structure of the catalyst and the microstructure of the obtained polymer has attracted much attention and broad interest in the field of transition metal-catalyzed olefin polymerization. Cycloalkyls, especially cyclohexyl, are known for their rich conformational change. In this contribution, we described the synthesis and characterization of a series of bulky yet flexible cycloalkyl substituted α-diimine ligands and the corresponding nickel and palladium catalysts. The thermostable nickel complexes in this system show high activity (up to 4.89 × 10 6 g mol −1 h −1 ) and can generate highly branched polyethylene (up to 112/1000C) with a high molecular weight (up to 54.4 × 10 4 g mol −1 ). The obtained polyethylene displays good elastic properties (SR value up to 77%) characteristic of thermoplastic elastomers. The flexible cycloalkyl substituted palladium complexes exhibit low to moderate catalytic activities (0.6–43.9 × 10 6 g mol −1 h −1 ), low to moderate molecular weights (0.93–31.23 × 10 4 g mol −1 ), and high branching density (87–122/1000C) for ethylene polymerization, while allowing appreciable comonomer incorporation (1.0–7.7%) for ethylene/MA copolymerization. Most interestingly, compared to the flexible cyclohexyl substituted α-diimine nickel and palladium catalysts, the rigid phenyl substituted catalysts generated polyethylene with much lower branching density in ethylene polymerization.